Desain dan Implementasi Sistem Monitoring Level Oli Hidrolik Excavator PC 1250 Berbasis IoT - Moch. Shofiyan Zuhri; Nurhadi (Jurnal Teknik Mesin Indonesia, 2024)
Excavator hydraulic oil shortages and leaks cause engine overheating, low power, shorter component life, and excavator breakdown so that the coal production chain at PT. Kalimantan Prima Persada is disturbed. Meanwhile, oil monitoring is still done manually. The research objective is to design and implement an IoT-based PC 1250 Excavator hydraulic oil level monitoring system that can monitor oil levels automatically and test the system response speed. The research was carried out experimentally to test the comparison of the response speed of two different microcontrollers, namely the ESP 8266 and ESP 32, which use an antenna and without an antenna. The IoT module is installed near the excavator operator to determine the hydraulic oil level. The research results show that the excavator hydraulic oil level monitoring tool is capable of operating with a response speed of < 1 second.